Properties of Portland cement pervious concrete - El-Tawil, Farrah Abdel Aziz (AUC Knowledge Fountain, 2014)
Portland Cement Pervious Concrete (PCPC) is an innovative type of concrete that contains little or no fine aggregates thus creating a substantial void content which allows concrete to be water permeable. PCPC thus can be used for drainage, recharging groundwater, reducing storm water and possibly filtering some pollutants. Proper employment of PCPC has been recognized by the U.S. Environmental Protection Agency (EPA) as a Best Management Practice. Yet, this type of concrete has not been yet considered in the Egyptian market. This study aims primarily at producing PCPC using local materials and achieving better understanding of mechanical properties, durability and potential applications. To meet that objective, concrete mixtures were prepared using 250, 350 and 450 kg of cement with different aggregates gradations, plasticizing admixtures, and silica fume. Fresh concrete tests as well as compressive and flexural strength tests were conducted. Water flow, chloride permeability, chemical durability, resistance to elevated temperature, and the potential of water purification and reduction of bacteria were examined. The results of this study investigation reveal that the PCPC can be produced using local materials and allow sizable flow of water throughout. PCPC has undergone a reduction of strength up to 48% when compared with conventional concrete. However, the reduction in strength still allows concrete to be produced at the lower bound of permits many of these mixtures to be used in structural concrete. Moreover, PCPC seems to possess a potential for water purification particularly for oil/grease contaminants. PCPC have witnessed an average reduction of 98.6% of TSS, 92.2% of bacteria, and 14.6% of lead when 98% of used vehicle oil was removed from the simulated water sample. Further research works as well as pilot trials need to be conducted to explore the full potential of PCPC in concrete applications requiring permeability of fluids and some purification of pollutants. Keywords: Pervious Concrete, No-fines, Porous Concrete, Storm-Water Management, and Water Purification